Identifikasi morfometri dan pola ruang taman setra di Kecamatan Kuta Utara, Kabupaten Badung, Provinsi Bali - Baskara, Putu Wiprah; Sugianthara, Anak Agung Gede; Asmiwyati, I Gusti Agung Ayu Rai (Jurnal Arsitektur Lansekap, 2021)
Bali island has three types of garden. One of garden’s types that exist in Bali is setra. Setra garden in Bali had been used for spiritual ceremonies like Ngaben. There were more than 1500 setra gardens that had not been yet identified in Bali. Therefore, identifying, collecting data, and mapping of setras garden were needed in analyzing the setras. Setras garden in which located in North Kuta sub-district was chosen in this research because there was not any database yet which was related to the setras especially for its space pattern and morphometry. This research aimed to identify the morphometry, space pattern, factors that affecting space pattern, and utilization of the setras in North Kuta sub-district. The research method used was survey method. This research used descriptive qualitative, and quantitative analisys. In the results, this research found that Kerobokan traditional village had the highest percentage number of setra garden which was 38,1%. Setra Tuka was located in the higest elevation (122,34 msal), while the 80% of setras was in the flat topography. The average area of setras garden in North Kuta was about 0,12 Ha. Direction of centre, and southeast was the most setras position (19%). The whole setras garden in North Kuta applied Tri Mandala concept as its space pattern and all of its space pattern was affected by tradition factor. For setras additional utilization, Caru and Ngereh have the highest percentage, while Ngelungah and Ngelangkir is more attractive activity for tourism.